LAPLACIAN MINIMUM COVERING EXTENDED ENERGY OF A GRAPH - SINDHUSHREE M V; INDUMATHI R S; AJAY C K; PUTTASWAMY; M R RAJESH KANNA (Utilitas Mathematica, 2025)
In the current research, we present the idea of the Laplacian minimum covering extended e´nergy of a graph EC(G) and calculate the Laplacian minimum covering extended energies of a complete graph, star graph, crown graph, cocktail party graph, and full bipartite graph.